Feasibility and effectiveness of a remote individual rehabilitation program for people with Parkinson's disease living in the Brazilian Amazon: a randomized clinical trial - Luciana Fernandes Pastana Ramos; Tamires de Cássia Santos Vilacorta-Pereira; Juliana dos Santos Duarte; Elizabeth Sumi Yamada; Bruno Lopes Santos-Lobato; Bruno Lopes Santos-Lobato (Frontiers in Neurology, 2023)
Parkinson's disease (PD) is a chronic and progressive neurodegenerative disorder, and the current treatment involves pharmacological intervention and physiotherapy. Telerehabilitation, which involves remote support and guidance for patients undergoing rehabilitation, can potentially improve access to physiotherapy services for people with Parkinson's disease, especially those who face geographic barriers to healthcare. The primary aim of this study was to assess the feasibility and efficacy of a telerehabilitation program for people with Parkinson's disease living in an underrepresented community of the Brazilian Amazon. We conducted a parallel-group, single-center, single-blind, phase 2 randomized controlled clinical trial involving 19 participants diagnosed with Parkinson's disease from Belém, Brazil. Participants were assigned to a 4-week individual telerehabilitation program or a booklet-based exercise program (control group). Assessments were conducted before the intervention, immediately after the intervention, and 4 weeks after the end of the intervention. We showed that our telerehabilitation program had high adherence among patients, with minimal adverse effects. Both telerehabilitation and booklet orientation reduced the time to complete the Timed Up and Go test. In conclusion, our telerehabilitation program was feasible and effective for people with Parkinson's disease in an Amazonian setting. This trial was registered at the Registro Brasileiro de Ensaios Clínicos (ReBEC) under the identifier: RBR-6sz837s.